The contemporary state faced with the functional triad: Values – norms – goods - Wilkin, Jerzy (Journal of Public Governance, 2018)
The main subject of analysis in this paper is the role of the state (government) in the functioning of economy and society in a post-socialist country. The frame of analysis is made up of the triad: values – norms – goods. The author presents the way economics approaches the category of value, stressing that this category has a very limited meaning in the theory of economics, but plays a significant role as a starting point in formulation of economic policy. However, norms could be treated as a concept related to institutional foundations of economy and social life. Achievements of institutional economics have a very significant impact on the development of contemporary economics, especially in the area of systemic transformation and in explaining the mechanisms of economic development. The author also touches upon the renaissance of the idea of “expanding government” in Poland and in other countries, and discusses the dangers associated with this tendency. He also describes the role of the state in relation to globalization and European integration.